Sex differences in heart rate responses to occupational stress. (2nd January 2020) - Lucas, Bethany; Grayson, Stella; Hamidu, Halimah; Han, Andrew; No, Sandra; Varghese, Ajay; Campisi, Jay
Abstract: Cardiovascular disease (CVD) remains the leading cause of disease burden globally and chronic stress is associated with increased risk of CVD. Recognition of chronic occupational stressors as a potential contributor to CVD highlights the need to recognize and prevent stress during work. The ubiquity of wearable technology devices to monitor health provides a new opportunity to noninvasively examine the cardiovascular system throughout a work shift. In the current study, we examined changes in heart rate (HR) during a work shift in a retail store setting using 23 healthy female and male subjects that differed in their physical fitness status. Subjects had their HR tracked via an Apple Watch during three typical work shifts. The results demonstrated an increase in HR during a work shift to a level observed during a moderate stressor (resting HR = 83.2 BPM ± 7.8; highest HR mean = 109.1 BPM ± 11.7; p  < .0001). Female subjects demonstrated a significantly elevated maximum HR, a larger change in HR, and a larger percent change in HR compared with males (all p  < .05). Physical activity status did not influence the observed changes in HR for females or males. Neither the time of day the work shift occurred nor the length of the shift modulated the observed pattern of HR changes. Collectively, our findings demonstrate the potential for wearables in biomedical research and personalized health.